O conhecimento didático-pedagógico para o coordenador pedagógico - Souza, Jesus Lopes de (2017)
This research investigates the role of the Pedagogical Coordinator (CP) in the training process of teachers, highlighting, above all, the didactic-pedagogical knowledge in the school context. The study assumes that didactics and pedagogical practices are decisive factors for the development of a meaningful learning by students, and for the recognition of the importance of the Pedagogical Coordinator as an articulator and coach for pedagogical practices that make this learning possible. Thus, the research proposes as main goal to investigate how the Pedagogical Coordinator articulates the educational practices and what is the contribution of his didactic-pedagogical knowledge in the continuing education of teachers. The empirical and qualitative research had as subjects of research three (03) Pedagogical Coordinators and six (06) teachers of the Public Basic School in the East zone of the city of São Paulo. The problem investigated was how the Pedagogical Coordinator uses their didactic-pedagogical knowledge when carrying out his work as coach of teachers, in order to provide a critical and reflexive intellectual formation. For this, the analysis is based on the theoretical currents of Libâneo (2013), Candau (2014), Placco, Almeida & Souza (2011), Tardif (2012), and Pimenta and Ghedin (2008). For the development of the field research, we used the questionnaire and the semi-structured interview as data-collection tools. Defined by Lüdke and André (2013), these tools allow considering the point of view of the professionals. As result, this research clearly indicates the relevance of didactic-pedagogical knowledge in the work of the Pedagogical Coordinator. Moreover, it points to the disarticulation of several actions at school as a consequence of lacking knowledge of the potential of didactic-pedagogical knowledge. This disarticulation embraces the setting up of the pedagogical proposal as well the processes of teaching and learning, and also the formation carried out by the Pedagogical Coordinators